2016
DOI: 10.1080/14615517.2016.1176413
|View full text |Cite
|
Sign up to set email alerts
|

We are all experts! Does stakeholder engagement in health impact scoping lead to consensus? A Dutch case study

Abstract: Faculty of earth and life sciences, VU University, amsterdam, the netherlands; f research centre Health and society, Wageningen University, Wageningen, the netherlands ABSTRACT Stakeholder engagement in Environmental Impact Assessment (EIA) and Health Impact Assessment (HIA) provides opportunities for inclusive environmental decision-making contributing to the attainment of agreement about the potential environmental and health impacts of a plan. A case evaluation of stakeholder engagement was carried out to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Our study revealed seven perceptions that were perceived to be most important: (1) social relations and interactions, (2) physical activity, (3) positive life attitude, (4) feeling in control, (5) healthy nutrition, (6) mental rest, and (7) the natural environment. This is in accordance with the findings in recent research on perceptions of health and lifestyle in other SES groups [ 33 , 59 , 60 , 61 , 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed seven perceptions that were perceived to be most important: (1) social relations and interactions, (2) physical activity, (3) positive life attitude, (4) feeling in control, (5) healthy nutrition, (6) mental rest, and (7) the natural environment. This is in accordance with the findings in recent research on perceptions of health and lifestyle in other SES groups [ 33 , 59 , 60 , 61 , 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is important to note, however, that if the municipality should undertake such an activity, the cost of the employees who organize and undertake the impact assessment will need to be added. The cost of PHIA (and HIA in general) has been identified as a major barrier to policy-level HIA [ 8 , 11 , 34 ], yet few studies have specifically reported on the actual costs of the process, leaving empirical uncertainty on the nature and extent of such barrier. This also creates uncertainty as to who is expected to fund the HIA and whether the decision to apply participatory approaches is based on financial affordances.…”
Section: Resultsmentioning
confidence: 99%
“…The use of participation in health care policy was underlined in the 1978 Alma-Ata Declaration IV of the World Health Organization (WHO) [ 6 ]: ‘The people have the right and the duty to participate individually and collectively in the planning and implementation of their health care’. However, participatory HIAs are still more an exception rather than a rule [ 7 ], even in countries with more experience in HIA practice, such as Australia [ 8 , 9 ], Italy [ 10 ], the USA [ 7 ] and the Netherlands [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inherent complexity and multidimensionality of assessing urban health demand evidence from multiple fields of knowledge and the engagement of stakeholders from different sectors [ 42 , 43 ]. Participation processes at the local level are broadly advocated and considered a current trend in urban health studies [ 44 ], not only because they provide a venue for inclusive decision-making [ 45 ] but more importantly contribute to efforts to reach agreement on an issue where plurality and heterogeneity of points of view arise [ 46 ]. Stakeholders have a wide range of social values and interests that result in different perceptions of what evidence is most useful and relevant to guide priority setting [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…; Participation and collaborative process: the participatory process is designed to promote shared understanding about urban health inequities while capturing multiple stakeholders’ values and perspectives, creating a collaborative environment that enables management of eventual conflicts of values and promote agreement. The aim is to create a joint learning experience as a means of creating space for all stakeholders to express their views [ 45 , 46 , 48 , 61 ]. Output validity: the outputs must be considered valid, that is, able to reflect what it is intended to reflect as relevant and meaningful for the specific context of evaluation and local situation (contextual validity), by the group of stakeholders actively engaged in the participatory process (participatory validity).…”
Section: Introductionmentioning
confidence: 99%